PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN MEMBELI PADA ANGKRINGAN SEMAR PALEMBANG - Agustina . M; Rinaldy . (JURNAL KOMPETITIF, 2019)
Therefore, this research aims to explain: the influence of service quality and location simultaneously on buying decisions at Angkringan Semar Palembang, the influence of service quality partially on buying decisions at Angkringan Semar Palembang, and the influence of location partially on buying decisions at Angkringan Semar Palembang. The sample in this research were consumers of Angkringan Semar Palembang amounting to 93 people using probability sampling (simple random sampling). Data were collected by questionnaire method and data analysis used was multiple regression analysis. Based on the results of this research indicate that service quality and location simultaneously have a positive and significant influence on buying decisions at Angkringan Semar Palembang, service quality partially have a positive and significant influence on buying decisions at Angkringan Semar Palembang, and location partially have a positive and significant influence on buying decisions at Angkringan Semar Palembang. Keywords : Quality Service, Location, Buying Decision